The intricacy of the human sexes - Voß, Heinz-Jürgen 1979- (Psychosozial-Verlag, 2021)
Translated by Anton Hieke Little defines human life more than the biological sexes. The concept of the binary sexes greatly affects our choices given in society, our income, and our visibility. Moreover, it is also the root for profound discrimination. Today, the idea that the binary sexes are nature-given is so intrinsically woven into the fabric of human life that we tend to forget just how modern the concept is. We also tend to forget that it does not have to be more than a bump on the path to a just society. Drawing from philosophical, historical, and biological perspectives, the author challenges existing beliefs in the inevitability of the binary nature of the human sexes. The study compellingly argues for the existence of many biological sexes, not merely two. It also outlines just how otherwise overcome assumptions still shape our seemingly modern understanding of the most basic classification of our societies: that of the biological sexes and the attributes piled upon them
Keywords: Geschlechtsunterschied; Biologie; Geschlechterforschung; Germany; Diversity; History; discrimination; science; Sex; sexuality; biological sex; binarity; variety